MICROBIOTA AND COSERVATION OF MILK - Menezes, Maria Fernanda Cáceres; Simeoni, Caroline Posser; Bortoluzzi, Débora; Huerta, Katira; Etchepare, Mariana; Menezes, Cristiano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Milk contais a series of compounds such as water, lipids, proteins, carbohydrates and trace elements. Its nutricional characteristics makes it an important substratum for the multiplication of microorganisms. The microbial contamination of the milk can take in two ways: the endogenous and exogenous, ranging quantitatively and qualitatively according to the existing conditions of hygiene. Raw milk kept under refrigeration temperatures for many days can contain bacteria of the following genera: Enterococcus, Lactococcus, Streptococcus, Leuconostoc, Lactobacillus, Microbacterium, Oerskovia, Propionobacterium, Micrococcus, Proteus, Pseudomonas, Bacillus and Listeria. May also be present some representatives of the group of fecal coliform. To eliminate or reduce to acceptable levels the microbiota of milk, heat treatments are of fundamental importance The objective of this review was to analyze and discuss the influence of the microbiota of milk in processing and storing of milk and preservation methods used to prolong the shelf life and ensure food safety and product quality.